Joint effect of docosahexaenoic acid intake and tobacco smoke exposure on learning disability in children and adolescents: a cross-sectional study from the NHANES database - Ling Liu; Xiuli Shu; Zijun Xu; Haibo Jiang (BMC, 2024)
Abstract Background Docosahexaenoic acid (DHA) has been reported to be associated with the children's neurodevelopment, who may be exposed to tobacco smoke simultaneously. The evidence about joint effect of DHA intake and tobacco smoke exposure on children and adolescents' learning disabilities (LD) was limited. The objective of this study was to assess the joint effect of DHA intake and tobacco smoke exposure on children and adolescents' LD. Methods A cross-sectional analysis of the NHANES 1999-2004 was performed. Children and adolescents aged 6-15 years old were included. The outcome was diagnosed by parental report of ever health professionals or school representative-identified LD. Dietary DHA intake data were obtained by food frequency questionnaire and tobacco smoke exposure levels were evaluated by serum cotinine levels. Weighted univariable and multivariate logistic regression analyses were conducted to determine the joint effect of DHA intake and tobacco smoke exposure on LD in children and adolescents, with odds ratios (ORs) and 95% confidence intervals (CIs). This joint association was further assessed after stratification by age, gender, body mass index, the history of attention deficit disorder and seen mental health professional. Results We identified 5,247 children and adolescents in present study, of whom 593 (11.30%) had LD. After adjusting covariates, we observed children and adolescents with DHA intake (OR = 0.76, 95%CI: 0.61-0.96) was related to lower incidence of LD; children who exposure to tobacco smoke was related to higher incidence of LD (OR = 1.54, 95%CI: 1.07-2.23); children and adolescents who exposure to tobacco smoke and without DHA intake were related to highest odds of LD (OR = 2.08, 95%CI: 1.37-3.17, P for trend = 0.042), that was, DHA and tobacco smoke exposure may have a joint effect on the odds of LD in children and adolescents. Subgroup analyses suggested this joint effect was robust especially among children and adolescents with normal & underweight BMI and without the history of attention deficit disorder and seen mental health professional. Conclusion Increasing the DHA intake and reducing tobacco smoke exposure may have a potential role in the prevention of LD in children and adolescents. This joint effect warrants further investigation by large-scale prospective study.